Co-frequency signal interference detection based on multiple antennas and multiple channels. Issue 1 (January 2021) - Shuai, Jianli; Wang, Zuo; Yang, Peng
Abstract: Co-frequency signal interference detection plays an absolute role in eliminating same-frequency interference. Eliminating same-frequency interference can improve signal-to-noise ratio and reduce communication errors. For an uncoded multi-antenna multi-channel system with Ni transmitting antennas and Nj receiving antennas, the algorithm is optimized on the basis of the QRD-M algorithm, and a depth-first QRD-M algorithm based on single-layer ML (ML-1 -IQRM algorithm), compared the performance of the ML-1-IQRM algorithm with the original QRD-M algorithm. The experimental results show that the ML-1-IQRM algorithm can better detect the interference of the same frequency signal.